PELAYANAN PENGADUAN PUBLIK PADA APLIKASI LAPOR DI KOTA BANJARMASIN (STUDI TENTANG STRATEGI KOMUNIKASI HUBUNGAN MASYARAKAT) - Laila Qadariah (UPT Publikasi Dan Pengelolaan Jurnal Universitas Islam Kalimantan MAB Banjarmasin, 2020)
The purpose of this study is to understand the public relations communication strategy (PR) in providing services to public complaints, To find out the factors that constrain the service to public complaints and to understand the efforts made by public relations (public relations) in overcoming service barriers to complaints public in Banjarmasin city government. The main focus of the research determined was the Banjarmasin City Government's Public Relations Communication Strategy in providing Services to Public Complaints. The message conveyed by the public relations department of public complaints, the effectiveness of the media or infrastructure owned by the Banjarmasin city government public relations, and what factors are hampering the implementation of the communication strategy. While data collection techniques are done by observation, interviews, and documentation. Analysis of the data used is an interactive model developed by Miles and Huberman. The results showed that the Socialization Strategy, the message, the effectiveness delivered and the factors hampering the implementation of the communication strategy that was carried out was going well, the socialization strategy could be via the internet and the mass media. around so as not to drag on.